(untitled) (The Peerian Journal, 2022)
This article shows the financial performance of the country’s insurance market and analyzes the investment activities of insurance companies operating in our country. The share of the insurance sector in the country’s Gross Domestic Product has been studied. It also highlights feedback from foreign and local scientists. The problems of the insurance market in Uzbekistan have been analyzed and the prospects for its development have been considered